The Effect of Leverage, Profitability, and Total Asset Turnover on Company Value With Liquidity as A Moderating Variable in Primary Consumer Goods Companies - Muhammad Saleh Nur Huda; Andy Dwi Bayu Bawono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The purpose of this study is to examine the effect of leverage on firm value, the effect of profitability on firm value, and the effect of total asset turnover on firm value; to analyze the effect of leverage on firm value with liquidity as a moderating variable; to examine the effect of profitability on firm value with liquidity as a moderating variable; and to analyze the effect of total asset turnover on firm value with liquidity as a moderating variable. This study employs a quantitative descriptive research design. The sample consists of 63 consumer goods companies that published complete financial statements in 2023 on the Indonesia Stock Exchange. Data analysis was conducted using multiple linear regression. The results indicate that leverage has a significant effect on firm value, and profitability also has a significant effect on firm value. However, total asset turnover does not have a significant effect on firm value. Liquidity does not moderate the effect of leverage on firm value, does not moderate the effect of profitability on firm value, and does not moderate the effect of total asset turnover on firm value. Asset utilization efficiency is not influenced by the level of liquidity in its relationship with firm value. Keywords:Leverage, Profitability, Total Asset Turnover, Firm Value, Liquidity